1976
DOI: 10.1111/j.1365-2133.1976.tb04336.x
|View full text |Cite
|
Sign up to set email alerts
|

The repair of impaired epidermal barrier function in rats by the cutaneous application of linoleic acid

Abstract: Epidermal barrier function in rats was experimentally impaired by two separate means, namely, by rendering the animals deficient in essential fatty acids and by evoking a primary cutaneous irritant response by treating with a solution of sodium laurate. Impaired barrier function was manifested by a greatly increased rate of transepidermal water loss. Application to the skin of sunflower seed oil, which is rich in linoleic acid, rapidly restored to normal the abnormally high rates of transepidermal water loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

1977
1977
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…597,598 Cutaneous absorption and metabolism of linoleic acid seemed largely responsible for the beneficial effects of sunflower-seed oil. 490,[598][599][600] Topical therapy with sunflower-seed oil has also been found to correct cutaneous signs of EFA deficiency (ie, normalization of TEWL, resolution of dermatitis) in humans, including premature infants.…”
Section: Topical Emollient Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…597,598 Cutaneous absorption and metabolism of linoleic acid seemed largely responsible for the beneficial effects of sunflower-seed oil. 490,[598][599][600] Topical therapy with sunflower-seed oil has also been found to correct cutaneous signs of EFA deficiency (ie, normalization of TEWL, resolution of dermatitis) in humans, including premature infants.…”
Section: Topical Emollient Therapymentioning
confidence: 99%
“…597,598 Cutaneous absorption and metabolism of linoleic acid seemed largely responsible for the beneficial effects of sunflower-seed oil. 490,[598][599][600] Topical therapy with sunflower-seed oil has also been found to correct cutaneous signs of EFA deficiency (ie, normalization of TEWL, resolution of dermatitis) in humans, including premature infants. 598,601,602 It has been ad-vanced that these beneficial effects may be due to increased metabolism of lipids in the epidermis, including active fatty-acid transport by keratinocytes, which makes it possible for even the immature epidermis of preterm infants to metabolize lipids derived from topically applied emollients and to utilize them as nutritional building blocks for the formation of a healthy, functional epidermal barrier.…”
Section: Topical Emollient Therapymentioning
confidence: 99%
“…22 ) also reported that dietary fish oil lacked the capacity to reverse the signs of dorsal epidermal disease characteristic of EFA deprivation. The decrease in water consumption by increased supply of the EPA concentrate to the 0.25EPA group may suggest that EPA has EFA-functional character in the skin, because the content of· LA, which prevents transepidermal water loss, 23,24) in the EPA concentrate was negligible (Table I).…”
Section: Discussionmentioning
confidence: 94%
“…Essential fatty acids (EFAs), in particular linoleic and γ-linolenic (18: 3n-6) acids, are essential for the construction and the repair of the skin lipidic barrier (Hansen and Jensen, 1985;Ziboh and Chapkin, 1987). Linoleic acid has a crucial role in the synthesis of acylglucosylceramides and thereby has the essential function in maintaining the integrity of the epidermal water permeability barrier Prottey et al, 1976). For these reasons, linoleic acid has been used for the treatment of acne vulgaris (Gareiss et al, 1996).…”
Section: Introductionmentioning
confidence: 99%